Das deutsche bürgerliche Drama auf der polnischen Bühne um die Jahrhundertwende (18. /19. Jh.) und die Zensur - Jurczyk, Ewa (Studia Germanica Posnaniensia, 2018)
This article deals with two main problems: the struggle of the Polish theatre-directors against the respective occupational powers and the work of foreign censorship in Poland. The respective (individual) heads of the Polish theatres tried to avoid being censored by mainly playing dramas for pure entertaiment. The censores were lulled into a true sense of security thus enabling the directors to stage more patriotic plays. The work of the censors will be shown with specific exemples from the German popular drama (e.g. Kotzebue, Iffland, Ziegler, Soden, Babo). The arts of censoring focussed mainly on certain characters, such as the father, the mother, the ruler and on respective instances of criticism directed against nobility and the government.